A Conspiracy of Dunces: Good Americans vs. A Cabal of Satanic Pedophiles? - Kaplan, Jeffrey (Terrorism and political violence, 2021)
While most observers classified the demonstrators called to Washington by President Trump as denizens of the far right, a closer examination of those arrested for entering the Capitol reveal a strikingly diverse group. Only a small percentage fit the description of members of the radical right. Rather, the most common thread was fealty to the President forged through adherence to QAnon and other conspiratorial beliefs.